Pengaruh Pengetahuan Penumpang tentang Prohibited Items terhadap Kepatuhan pada Security Check Point di Bandar Udara Internasional Adi Soemarmo Boyolali Jawa Tengah - Kusumawati, Candra; Albanna, Faiz (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In accordance with Law No. 1 of 2009 the purpose of the implementation of flights is to realize the operation of flights that are safe, secure, fast, smooth, orderly, orderly and comfortable. Passenger concern can be in the form of knowledge and compliance with aviation security and safety procedures, especially during security checks at the Security Check Point. Therefore, this study aims to determine the effect of passenger knowledge on compliance. This study uses three independen variabels, namely Analytical Thinking Knowledge (X1), Conceptual Thinking (X2) and Expertise (X3) for the dependen variabel, namely Compliance (Y) using a quantitative method that uses a questionnaire to collect data that is distributed directly to 100 passengers at Adi Soemarmo airport using a non-probability sampling technique which was then assisted by using the SPSS data processing application Version 20. This research was conducted at Adi Soemarmo International Airport Boyolali, Central Java on December 5 2022 to January 5 2023. The results of this study indicate that the Analytical Thinking (X1) and Expertise (X3) variabels have an influence on the Compliance variabel (Y) while the Conceptual Thinking variabel (X2) has no effect on the Compliance variabel (Y) as evidenced by the t test. The f test shows that the effect of passenger knowledge on compliance is 40.2%. Keywords: Knowledge, Analytical Thinking, Conceptual Thinking, Expertise, Compliance